KONTRIBUSI PENDIDIKAN DALAM KELUARGA TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SDN 03 TARAM KECAMATAN HARAU - Putri Hayani; Muhammad Hafizh (El-Rusyd, 2020)
The problem in this research is the extent of the contribution of education in the family to the learning outcomes of Islamic religious education in primary schools. the purpose of this study was to determine the education in the family, earning outcomes as well as the contribution of education.and the finally learning student. The resoerched this descrition of qualitaty the The shape and the family business in the education of children in the family does not happen is based on data and facts in the field, namely toidak the interaction within the family because of factors were less sociable family habits . The student learning outcomes SDN 03 Taram generally based on data analysis in general is beingThe results of studying Islamic education is influenced by education in kerluarga students of SDN 03 due to low learning outcomes in general and is affected by other factors that occur in the life of society